The Path to Balance: Cognitive and Islamic Counseling Techniques in Overcoming Stress - El-Hayatu Syam, Arini Sobri (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
In navigating life in the complex modern era which causes feelings of depression and stress disorders experienced by individuals, spiritual intelligence becomes very important. Stress is a condition where a person feels pressured and this pressure affects his or her emotional side, body, and behavior because the individual is less able to overcome the challenges and problems they are going through. Stressful events can be overcome in several ways, one of which is by applying Islamic guidance and counseling by praying sincerely, reciting dhikr to Allah SWT with a sense of peace, praying with all your heart, and reading the Koran. Therefore, this research focuses on discussing theoretical comparisons of Western counseling approaches, namely cognitive counseling and Islamic counseling approaches in efforts to deal with stress. Meanwhile, this type of research uses descriptive qualitative research. The technique used in data collection in this research is content analysis research. The content analysis in question consists of previous research, journal articles, proceedings papers, previous research, and several books related to holy words, the meaning of holiness, and the appreciation of prayer. The results of this study indicate that a combination of cognitive counseling techniques and Islamic principles can effectively help individuals overcome stress. In the research process, the writer recommended implementing similar counseling models in various settings, including educational and mental health institutions, to achieve better results in stress management.